599 Clinicians' perceptions regarding their roles and functioning within a New Zealand regional trauma system. (1st September 2016) - Kool, Bridget; Lee, Henrietta; Ameratunga, Shanthi; Lawrenson, Ross; Scott, Nina; Christey, Grant
Abstract : Background: The effectiveness of trauma systems in reducing injury mortality is well established. This study aimed to explore clinicians' perceptions of the quality of clinical trauma care delivered in New Zealand's only regional trauma system. Methods: An anonymous online survey of clinicians providing trauma care in five hospitals in the Midland region of New Zealand was conducted in 2014. The region has a population of around 799, 000 people and a predominantly rural environment. The survey sought information on clinicians' perceptions regarding: their level of comfort in managing trauma; awareness of regional and local trauma care guidelines; quality of trauma care at their hospital and the region; presence/absence of inequities in care; and the potential benefits of Computerised Decision Support Systems (CDSS). Results: 23% (74/319) of clinicians invited took part, the majority of whom were medical specialists, had >5 years of experience treating trauma patients, and attended to trauma patients less than twice weekly. Linear regression analyses indicated that having >5 years of experience treating trauma patients (p = 0.04) and holding a senior position (p = 0.04) were significant predictors in clinicians' comfort level in managing major trauma patients. Two-thirds of clinicians felt there were gaps in trauma care delivery in both their hospital and the Midland region with senior clinicians more likely to give a lower rating to the quality of the regional system. 35% of clinicians 'often/very often' experience difficulty in engaging with relevant specialities for trauma patients. Over 75% of respondents answered 'rarely'/'never' when asked how often their healthcare organisation treats people unfairly based on a range of factors (e.g. ethnicity, socioeconomic status). While their direct experience with CDSS was minimal, over half the clinicians considered CDSS to be a useful tool to guide the diagnosis and management of trauma patients. Conclusion: The study has highlighted some perceived gaps in trauma care in the region, and a lack of confidence among junior clinical staff in managing trauma patients. An opportunity exists to investigate the integration of CDSS into clinical trauma care to help guide the delivery of evidence-based care.